Collected Works of Paul Valery, Volume 14 : Analects - Valery, Paul, 1871-1945 (Bollingen series ;, 2015)
Grouped together in this book are several smaller volumes and plaquettes in which Valery had published selections of his shorter prose writings: aphorisms, moral reflections, poetic observations, flashes of wit or fancy, even jokes--a variety of remarks and impressions, many of them first recorded in his Notebooks.